Will the machine perfusion of the liver increase the number of donor organs suitable for transplantation? - V. A. Gulyaev; S. V. Zhuravel’; M. S. Novruzbekov; O. D. Olisov; K. n Lutsyk; M. G. Minina; A. S. Mironov; N. K. Kuznetsova; K. M. Magomedov; M. Sh Khubutiya (Трансплантология (Москва))
Worldwide, there is a trend towards an increase in the number of patients waiting for liver transplantation, despite an increase in the total number of liver transplantation operations. Solving the problem of donor organ shortage is possible through the use of organs from marginal donors: organs removed after cardiac arrest, organs with a high percentage of steatosis, organs from donors over the age of 60 years. The main reason for refusing to use them is the risk of severe complications and an unfavorable outcome of the operation. Static cold preservation today is the main method of protecting donor organs from thermal damage, which possesses rather effective protective properties. At the same time, the duration of cold preservation has a limited time interval. There is always uncertainty about the viability of the organ. Modern methods for assessing donor organs such as donor history, laboratory data, visual examination and morphology, do not reliably predict liver function after transplantation. In this regard, the development of methods for preserving the organ after removing, which do not degrade the quality of the organ or even are capable of restoring the lost functions, is relevant. The machine perfusion of the liver is one of the new concepts aimed at solving this problem. The article highlights the international experience of using the machine perfusion of the donor liver over the past 15 years. Machine perfusion is a promising trend of transplantation development, which allows reducing the shortage of donor organs and improving their quality.